ANALISIS DEL PARTO NORMAL VS CESARIA Y SU INCIDENCIA ECONOMICA EN EL HOSPITAL NIVEL DOS DEL INSTITUTO ECUATORIANO DE SEGURIDAD SOCIAL DE LA CIUDAD DE BABAHOYO DE LA PROVINCIA DE LOS RIOS - VANESSA DELGADO CRUZ (2008)
ANALYSIS OF NORMAL BIRTH VS CAESARIA AND ITS ECONOMIC IMPACT IN THE LEVEL TWO HOSPITAL OF THE ECUADORIAN INSTITUTE OF SOCIAL SECURITY OF THE CITY OF BABAHOYO OF THE PROVINCE OF LOS RIOS